Boosting Cholinergic Activity in Gustatory Cortex Enhances the Salience of a Familiar Conditioned Stimulus in Taste Aversion Learning. - Clark, Emily Wilkins; Bernstein, Ilene L. (Behavioral Neuroscience, 2009)
The cholinergic system is important for learning, memory, and responses to novel stimuli. Exposure to novel, but not familiar, tastes increases extracellular acetylcholine (ACh) levels in insular cortex (IC). To further examine whether cholinergic activation is a critical signal of taste novelty, in these studies carbachol, a direct cholinergic agonist, was infused into IC before conditioned taste aversion (CTA) training with a familiar taste. By mimicking the cholinergic activation generated by novel taste exposure, it was hypothesized that a familiar taste would be treated as novel and therefore a salient target for aversion learning. As predicted, rats infused with the agonist were able to acquire CTAs to familiar saccharin. Effects of carbachol infusion on patterns of neuronal activation during conditioned stimulus-unconditioned stimulus pairing were assessed using Fos-like immunoreactivity (FLI). Familiar taste-illness pairing following carbachol, but not vehicle, induced significant elevations of FLI in amygdala, a region with reciprocal connections to IC that is also important for CTA learning. These results support the view that IC ACh activity provides a critical signal of taste novelty that facilitates CTA acquisition. Reprinted by permission of the publisher.